COVID-19 outbreak: How do human resource management practices affect employee well-being? - Johar, Elaina Rose; Rosli, Nadzirah; Mat Khairi, Siti Murni; Shahruddin, Shafiq; Mat Nor, Norzanah (Frontiers in Psychology, 2022)
The study examines the effect of human resource practices (HRPs), including ability, motivation, and opportunity practices, on employee well-being (EWB) in the Malaysian environment during the COVID-19 pandemic. This research surveyed 154 service sector employees at Klang Valley, Malaysia. The data were analysed using structural equation modelling. Based on the Ability, Motivation and Opportunity (AMO) theory, the results indicate that motivation and opportunity practices have a significant positive effect on EWB, whereas ability enhancing practices have an insignificant effect. Human resource policies and practices must foster a conducive yet contented work environment, and leaders must provide opportunities and motivation for employees to participate actively in the workplace. By doing so, the organisation’s value of human resources can be significantly increased, and the organisation’s goals can be achieved while employees’ overall well-being is enhanced, resulting in a win-win situation. This study uncovers the important roles of AMO practices that can effectively increase EWB.